Fitness, knee function and competition performance in professional alpine skiers after ACL injury - Csapo, R.; Hoser, C.; Gföller, P.; Raschner, C.; Fink, C. (Journal of Science and Medicine in Sport, 2019)
Objectives: To assess the fitness of elite alpine skiers during recovery from anterior cruciate ligament (ACL) reconstruction and changes in performance level after return to competition. Design: Retrospective cohort study. Methods: The database of a specialized sports clinic was screened for professional alpine skiers with a history of ACL rupture and reconstruction. Strength and further functional tests as well as questionnaire data reflecting the athletes` subjective perception of pain, function in activities of daily living and physical activity levels were extracted. The website of the International Ski Federation (FIS) was used to obtain FIS points reflecting the competition performance level prior to injury, after return to competition as well as one year later. Results: Questionnaire data revealed the highest patient satisfaction. Measurements performed 161.5 ± 24.2 days after surgery showed persistent muscle strength and power deficits, which primarily affected the knee extensor muscles and were more pronounced following reconstruction using quadriceps as compared to hamstring tendon grafts. FIS points increased immediately after return to competition (364.3 ± 142.5 days post-reconstruction) but dropped below pre-injury levels within the first year. Conclusions: ACL injuries sustained by professional skiers entail muscle strength and power deficits that persist for more than five months after surgery. The rate of recovery of knee extensor muscle function may be slower following ACL reconstruction using quadriceps tendon grafts. On average, athletes returned to competition within one year after surgery and succeeded in surpassing their baseline performance level within the first year after return to competition.